Financial viability of Cocoa agroforestry systems in Ghana: The case of Sefwi Wiawso District - Nunoo, Isaac (2015)
A thesis submitted to the Department of Agriculture Economics, Agribusiness and Extension Kwame Nkrumah University of Science and Technology In Partial Fulfillment of the Requirements for the Degree Of Masters of Philosophy in Agricultural Economics. 2015